PEMANFAATAN MODAL SOSIAL SEKOLAH LAUT DI KOTA TEGAL - Larasati, Shofin; Astutik, Dwi; Trinugraha, Yosafat Hermawan (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
The problem of dropping out of school is a serious problem in the world of education so it must be resolved so that everyones basic needs for education are met. One way is through community-based non-formal education institutions, namely the Community Learning Activity Center (PKBM), such as PKBM Sakila Kerti which is part of the Sea School in the coastal area of Tegal City. This research aims to find out how the PKBM Sakila Kerti Sea School gets support and assistance from various parties so that it is able to meet the educational needs of children, especially coastal children who have dropped out of school. The research method used is qualitative with a case study approach. Data was obtained from interviews with several parties at the PKBM Sakila Kerti Sea School, parents and the community, as well as the results of researchers observations. The research results show that the way the PKBM Sakila Kerti Sea School gets support and assistance from various parties is by utilizing the schools social capital. Social capital consisting of networks, norms and trust is able to solve educational problems in Tegal City, especially in efforts to fulfill the educational needs of coastal children. The network formed at the PKBM Sakila Kerti Sea School is supported by cooperation, both among the school community and cooperation between the school and partners. In the network that is formed there are also norms that contain rules or regulations to control a persons behavior and in establishing social relationships. Mutual trust in each other is also very important to strengthen social networks and cooperation, as well as implement norms as well as possible to accompany the development of the PKBM Sakila Kerti Sea School.Permasalahan putus sekolah menjadi persoalan yang serius dalam dunia pendidikan sehingga harus diselesaikan agar kebutuhan dasar setiap orang terhadap pendidikan terpenuhi. Salah satunya adalah melalui lembaga pendidikan nonformal yang berbasiskan masyarakat, yaitu Pusat Kegiatan Belajar Masyarakat (PKBM), seperti PKBM Sakila Kerti yang berada di wilayah pesisir pantai di Kota Tegal. Penelitian ini bertujuan untuk mengetahui bagaimana cara PKBM Sakila Kerti mendapatkan dukungan dan bantuan dari berbagai pihak sehingga mampu memenuhi kebutuhan pendidikan anak, khususnya anak pesisir yang putus sekolah. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Data diperoleh dari hasil wawancara dengan beberapa pihak PKBM Sakila Kerti, orang tua murid, dan masyarakat, serta hasil observasi peneliti. Hasil penelitian menunjukkan bahwa cara PKBM Sakila Kerti mendapatkan dukungan dan bantuan dari berbagai pihak adalah dengan memanfaatkan modal sosial yang dimiliki PKBM Sakila Kerti. Modal sosial yang terdiri dari jaringan, norma, dan kepercayaan mampu menyelesaikan permasalahan pendidikan di Kota Tegal khususnya dalam usaha pemenuhan kebutuhan pendidikan anak pesisir. Jaringan yang terbentuk di PKBM Sakila Kerti didukung dengan adanya kerja sama, baik di antara warga sekolah serta kerja sama antara sekolah dengan mitra. Dalam jaringan yang terbentuk juga terdapat norma-norma yang berisi aturan-aturan atau tata tertib untuk mengontrol perilaku seseorang maupun dalam menjalin hubungan sosial. Rasa saling percaya satu sama lain dalam hal tersebut kemudian perlu ditingkatkan agar jaringan sosial dan kerja sama dapat terus bertahan mengiringi perkembangan PKBM Sakila Kerti.